Pengaruh Pembelajaran Projek Penguatan Profil Pelajar Pancasila (P5) terhadap Karakter Siswa Kelas VIII di SMP Negeri 2 Kubung - Febriani, Armi; eka putri , Desi armi; Ikhwan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the extent of the influence of the Pancasila Student Profile Strengthening Project on the Character of Class VIII Students at SMP Negeri 2 Kubung. This type of research is quantitative research. The population and sample in this study were class VIII students at SMP Negeri 2 Kubung in the 2023/2024 academic year, totaling 70 people. Sampling was carried out using the total sampling technique. Data collection techniques by means of observation, questionnaires and documentation. The data analysis technique used in this study is descriptive. The results of the study indicate that the Pancasila student profile strengthening project on student character shows a value (Sig). 0.00 <0.05 and the t count value is 7.667 while the t table value is 1.667. This means that t count> t table means H0 is rejected and Ha is accepted. Based on the results, it can be concluded that there is a positive and significant influence of the Pancasila student profile strengthening project on the character of class VIII students at SMP Negeri 2 Kubung. The magnitude of the influence of the Pancasila student profile strengthening project on student character is 46.4%.